Biocidal efficacy of tutin and its influence on immune cells and expression of growth‐blocking and neuroglian peptides in Mythimna separata (Lepidoptera: Noctuidae). Issue 1 (9th April 2021) - Li, Feifei; Cui, Jun; Shaheen, Tayyab; Tang, Guanghui; Wang, Tao; Woolfley, Tracy; Li, Menglou
Abstract: Mythimna separata Walker (Lepidoptera: Noctuidae) is one of the major pests that can cause severe damage to grain crops. The development of low‐toxicity and high‐performance botanical insecticides is becoming the focus of new pesticide research to control M. separata . Tutin, a sesquiterpene lactone compound obtained from Coriaria sinica Maxim, a native Chinese poisonous plant, has antifeedant, absorption, and stomach poisoning against a variety of pests. To understand the toxic effect of tutin on M. separata larvae, we set out to determine their antifeedant, mortality, paralysis, weight change, and to examine the spreading of M. separata hemocytes under different concentrations of tutin treatment. Tissue distribution of the immune‐associated gene growth‐blocking peptide ( GBP ) and neuroglian peptide ( Nrg ) was detected by reverse transcription polymerase chain reaction (PCR). Furthermore, real‐time quantitative PCR was carried out to determine the expression profiles of GBP and Nrg after different concentrations of tutin stimulation. Our results revealed that tutin exhibited significant antifeedant and insecticidal activities, paralysis, weight loss to M. separata . Besides, tutin significantly influenced on the morphology of hemocytes and enhanced the expression of GBP and Nrg in M. separata . Abstract : This study determined the effect of tutin on antifeedant, mortality, paralysis, and weight loss to Mythimna separata . After exposure to tutin, the spreading of M. separata hemocytes was significantly increased, and the transcripts of immune‐associated genes were upregulated, which were detected by real‐time quantitative PCR. Research Highlights: 1. Tutin induced antifeedant, mortality, paralysis, and weight loss to M. separata. 2. The cellular immune response of M. separata can be stimulated by tutin. 3. The expression patterns of GBP and Nrg in M. separata were determined.